Sound Particles and Microsonic Materialism. - Whitelaw, Mitchell (Contemporary Music Review, 2003)
The cultural imagination of data is crucial in a society increasingly enmeshed in the datasphere. In writing around recent experimental audio ("microsound"), sound data are frequently described in terms of matter, through the figure of the sound particle. Here this material metaphor is examined in detail, and critiqued for misrepresenting the crucial relationship between sound, matter and data, which is at the core of this field of practice.